2004
DOI: 10.1590/s0036-46652004000400007
|View full text |Cite
|
Sign up to set email alerts
|

The perception, beliefs and practices toward genitourinary schistosomiasis by inhabitants of selected endemic areas (Edo/Delta States) in south-eastern Nigeria

Abstract: Well-structured questionnaire on the perception, impression and response to genitourinary bilharziasis (Genitourinary schistosomiasis) was administered and explained in local languages: 'Igbo' 'Esan' 'Ezon' Itshekiri and Bini to 33815 inhabitants of selected endemic areas in south-eastern Nigeria from January, 1999 to December, 2001. Out of this number, 3815 (11.3%) were properly filled and returned. About 42.0% of the inhabitants admitted knowledge of the disease, while 14 (0.4%) knew about the aetiologic age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 8 publications
0
11
2
Order By: Relevance
“…However, these findings contradict the lack of knowledge observed in Nigeria where fewer subjects were aware of urinary schistosomiasis infection [10]. Our respondents had acquired primary school education that signifies the impact of basic school education on awareness of schistosomiasis.…”
Section: Discussioncontrasting
confidence: 90%
“…However, these findings contradict the lack of knowledge observed in Nigeria where fewer subjects were aware of urinary schistosomiasis infection [10]. Our respondents had acquired primary school education that signifies the impact of basic school education on awareness of schistosomiasis.…”
Section: Discussioncontrasting
confidence: 90%
“…The levels of haematuria and proteinuria in the study were low and did not conform favourably with other studies where as high as 40-80% had been reported [3,44,11]. It is notable from that a combination of symptoms, such as morbidity indicators will be useful for the purpose of rapid epidemiological survey in any wide endemic area.…”
Section: Discussioncontrasting
confidence: 60%
“…The PedsQL tool may not capture the specific experience associated with schistosomiasis; there may be cultural or language barriers that limit the assessment of infection impact and chronic manifestations of schistosomiasis may be accepted as normal health status. [57][58][59][60] Therefore, a person might not perceive themselves to have a decreased quality of life on questioning or language may interfere with the interpretation of the impact. These concerns suggest that qualitative studies aimed at determining if and in what capacity quality of life in children is affected by schistosomiasis are warranted.…”
Section: Discussionmentioning
confidence: 99%